Dinamika Sosio-Ekonomi dan Paradoks Patron-Klien: Strategi Bertahan Petani Cabai di Wilayah Pesisir Gorontalo - Riswan Mahmud Adam; Merita Ayu Indrianti; Moh. Muchlis Djibran (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to explore the socio-economic structures underlying the economic behavior of chili farmers in Batudaa Pantai Subdistrict, Gorontalo Regency, with a focus on patron-client relationships as a rational coping mechanism. Using a mixed-methods approach with 60 proportionally selected respondents, this study analyzes how asymmetries in access to capital and markets create a weak bargaining position for farmers. The findings reveal a “stability paradox”: although quantitative risk analysis using the Coefficient of Variation (CV) indicates low levels of production, cost, and income risk (CV < 0.5), farmers remain trapped in a price-taker position. Relationships with middlemen (tengkulak) have transformed from mere economic transactions into social bonds of “debt of gratitude.” For farmers, patrons serve as providers of emergency liquidity and market guarantors amid horticultural price volatility. However, this systemic dependence hinders economic independence and capital accumulation at the producer level. This study recommends institutional restructuring through a new cooperative model capable of assuming the patron’s role more equitably to break the chain of structural dependence.